Anlotinib Enhances the Antitumor Activity of High-Dose Irradiation Combined with Anti-PD-L1 by Potentiating the Tumor Immune Microenvironment in Murine Lung Cancer. (1st February 2022) - Yuan, Meng; Zhai, Yirui; Men, Yu; Zhao, Maoyuan; Sun, Xin; Ma, Zeliang; Bao, Yongxing; Yang, Xu; Sun, Shuang; Liu, Yunsong; Zhang, Wanting; Hui, Zhouguang
Abstract : Background . Radioimmunotherapy has become one of the most promising strategies for cancer treatment. Preclinical and clinical studies have demonstrated that antiangiogenic therapy can improve the efficacy of immunotherapy and sensitize radiotherapy through a variety of mechanisms. However, it is undefined whether angiogenesis inhibitors can enhance the effect of radioimmunotherapy. In this study, we aim to explore the role of anlotinib (AL3818) on the combination of radiotherapy and immune checkpoint inhibitors in Lewis lung carcinoma mouse. Methods . C57BL/6 mouse subcutaneous tumor model was used to evaluate the ability of different treatment regimens in tumor growth control. Immune response and immunophenotyping including the quantification and activation were determined by flow cytometry, multiplex immunofluorescence, and multiplex immunoassay. Results . Triple therapy (radiotherapy combined with anti-PD-L1 and anlotinib) increased tumor-infiltrating lymphocytes and reversed the immunosuppressive effect of radiation on the tumor microenvironment in mouse model. Compared with radioimmunotherapy, the addition of anlotinib also boosted the infiltration of CD8 + T cells and M1 cells and caused a decrease in the number of MDSCs and M2 cells in mice. The levels of IFN-gamma and IL-18 were the highest in the triple therapy group, while the levels of IL-23, IL-13, IL-1 beta, IL-2, IL-6, IL-10, and Arg-1 were significantly reduced. NF- κ B, MAPK, and AKT pathways were downregulated in triple therapy compared with radioimmunotherapy. Thus, the tumor immune microenvironment was significantly improved. As a consequence, triple therapy displayed greater benefit in antitumor efficacy. Conclusion . Our findings indicate that anlotinib might be a potential synergistic treatment for radioimmunotherapy to achieve better antitumor efficacy in NSCLC patients by potentiating the tumor immune microenvironment.